Melacak Akar Perang Suci: Perkembangan Ide Jihād dalam Tradisi Islam - Ismatu Ropi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
This article examines Reuven Firestone’s book, Jihad: The Origin of Holy War in Islam (New York: Oxford University Press, 1999), within the broader context of the historical and scholarly discourse on religious wars. The study of holy war as a religiously justified conflict remains relatively new in academic traditions, with early foundational works such as Julius Wellhausen’s Prolegomena to the History of Ancient Israel (1885) inspiring later research. Comparative studies on the Judeo-Christian tradition have been explored by scholars such as Susan Niditch, Roland Bainton, and James A. Brundage. Meanwhile, Western scholarly attention to religious war in Islam began in the early 20th century with works by Gardner (1912) and Stephen van Rensselaer Trowbridge (1913), followed by seminal studies such as Majid Khadduri’s War and Peace in the Law of Islam (1955) and Rudolph Peters’ Jihad in Mediaeval and Modern Islam (1977). The term